2016
DOI: 10.1111/jne.12371
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of the Vasopressin Promoter Explains Physiological Ability to Regulate Vasopressin Transcription in Dehydration and Salt Loading States in the Rat

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.The synthesis of arginine vasopressin (AVP) in the supraoptic nucleus (SON) and paraventricular nucleus (PVN) of the hypothalamus is sensitive to increased plasma osmolality and a decreased blood volume, and thus is robustly increased by both dehydration (increased plasma osmolality and decreased blood volume) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
(105 reference statements)
2
7
1
Order By: Relevance
“…In addition, our findings from in vitro cell cultures hinted that methylation could be important in regulating Creb3l1 expression in different cell-types of the PVN, namely AVP and OT neurones, particularly as Creb3l1 expression increases exclusively in AVP neurones by DH (Greenwood et al, 2014 ). We recently described altered methylation patterns of the Avp promoter with DH in the SON and in this study we observed decreased expression of the demethylating enzyme ten-eleven translocation 2, Tet2, by DH and SL in support of methylation changes in the hypothalamus (Greenwood et al, 2016a ). Interestingly there was an absence of methylation marks on this region of the Creb3l1 promoter in vitro in the PVN.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In addition, our findings from in vitro cell cultures hinted that methylation could be important in regulating Creb3l1 expression in different cell-types of the PVN, namely AVP and OT neurones, particularly as Creb3l1 expression increases exclusively in AVP neurones by DH (Greenwood et al, 2014 ). We recently described altered methylation patterns of the Avp promoter with DH in the SON and in this study we observed decreased expression of the demethylating enzyme ten-eleven translocation 2, Tet2, by DH and SL in support of methylation changes in the hypothalamus (Greenwood et al, 2016a ). Interestingly there was an absence of methylation marks on this region of the Creb3l1 promoter in vitro in the PVN.…”
Section: Discussionsupporting
confidence: 76%
“…Treatment with Aza alone increased Avp expression, and when combined with FSK this increase in expression was markedly enhanced. To demonstrate that increased Avp expression was not the result of demethylation of the Avp promoter as we have previously reported (Greenwood et al, 2016a ), we overexpressed Creb3l1 in N2a cells and were able to successfully reproduce this response. Therefore, methylation strongly influences the actions of Nr4a1 as a transcriptional regulator of the Creb3l1 gene in vitro .…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…This has led some to suggest that deficits in mechanisms controlling transcription, mRNA stability, or translation in the aging SON magnocellular neurons may be responsible ( Lucassen et al., 1997 ). Moreover, we recently showed that dehydration initiates the formation of new methylation marks on the rat Avp promoter ( Greenwood et al., 2016a ), suggesting that altered methylation patterns could lie beneath these transcriptional changes in aging AVP neurons.…”
Section: Introductionmentioning
confidence: 99%